The Effect of Play Therapy Based on Cognitive-behavioral Approach on Academic Achievement and Self-esteem of Students with Special Learning Disabilities - Farzaneh Abbaslo (پژوهان, 2020)
Background and Objectives: The aim of this study was to determine the role of play therapy based on cognitive-behavioral approach in increasing self-esteem and improving academic performance of students with special learning disabilities (inadequacy and dyslexia). Materials and Methods: The statistical population of the present study consists of 415 primary school male students of Shahid Danesh School in Tehran, who were studying in the academic year of 1996-97. The sample group consisted of 44 students with dyslexia and dyslexia by simple random sampling and were replaced in the experimental and control groups. The research design was experimental (pre-test and post-test with control group). After performing the pre-test of Colorado Learning Disabilities Questionnaire (CLDQ) and Cooper-Smith Self-Esteem Questionnaire for both groups, the experimental group for 2 weeks, in 8 sessions of 45 minutes under play therapy training with cognitive behavior approach developed by Schaffer were included and after this period, post-test was performed for both groups. Data were analyzed using analysis of covariance (ANCOVA). Results: The results showed that play therapy significantly increased the level of self-esteem at the level of P <0.05 and improved the performance of mathematics and reading of students with disability at the level of P <0.05 and dyslexia at the level of P <0.01. Conclusions: The results showed that play therapy based on cognitive-behavioral approach as an effective method has a positive effect on increasing students' self-esteem and academic achievement and leads to a reduction in math and reading problems in students with disorders. It becomes special learning.